In-medium Spectral Functions in a Coarse-Graining Approach. (March 2015) - Endres, Stephan; van Hees, Hendrik; Weil, Janus; Bleicher, Marcus
Abstract: We use a coarse-graining approach to extract local thermodynamic properties from simulations with a microscopic transport model by averaging over a large ensemble of events. Setting up a grid of small space-time cells and going into each cell's rest frame allows to determine baryon and energy density. With help of an equation of state we get the corresponding temperature T and baryon-chemical potential μB . These results are used for the calculation of the thermal dilepton yield. We apply and compare two different spectral functions for the ρ meson, firstly a calculation from hadronic many-body theory and secondly a calculation from experimental scattering amplitudes. The results obtained with our approach are compared to measurements of the NA60 Collaboration. A relatively good description of the data is achieved with both spectral functions. However, the hadronic many-body calculation is found to be closer to the experimental data with regard to the in-medium broadening of the spectral shape.